Enhancing the extraction efficiency of beneficial compounds from Tapirira guianensis fruit using ultrasound-assisted extraction and choline chloride deep eutectic solvent - Mar, Josiana Moreira; Carolino, Adriano de Souza; Neves, Kidney de Oliveira Gomes; Corrêa, Renilto Frota; Machado, Marcos Batista; Rocha, Daniel de Queiroz; Kinupp, Valdely Ferreira; Sanches, Edgar Aparecido; Campelo, Pedro Henrique; Bezerra, Jaqueline de Araújo (Food Science and Technology, 2025)
In recent decades, a new class of solvents known as natural deep eutectic solvents has emerged. In this study, the efficacy of different natural deep eutectic solvents, prepared by ultrasound-assisted synthesis, was evaluated for extracting bioactive compounds from Tapirira guianensis fruits. A total of seven natural deep eutectic solvents systems, combining choline chloride with various hydrogen bond donors (carboxylic acids, alcohols, and sugars), were analyzed for total phenolic content and antioxidant activity. The results showed that carboxylic acid-based natural deep eutectic solvents were the most efficient, with the best results obtained using choline chloride/citric acid/glycerol (Stap7) > choline chloride/citric acid (Stap1) > choline chloride/lactic acid (Stap2), yielding total phenolic contents of 715.7 ± 1.1, 648.5 ± 1.2, and 630.7 ± 0.7 mg GAE/g, respectively. Ultrasonic extraction with 40% (v/v) eutectic mixtures showed that combinations with citric acid were more effective, producing extracts with high concentrations of polyphenols and antioxidant potential. The antioxidant activity, measured by 2,2-Diphenyl-1-picrylhydrazyl, 2,2′-Azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt, and ferric-reducing antioxidant power assays, showed a similar trend. Spectroscopic analysis (nuclear magnetic resonance) identified gallic acid and 5-hydroxyvanillin, providing structural details of the extracts. Macro- and micronutrient analysis revealed some elements below detection limits. Therefore, these extracts can be used directly for application development without additional isolation.